Antifungal activity of GRAS salts against Lasiodiplodia theobromae in vitro and as ingredients of hydroxypropyl methylcellulose-lipid composite edible coatings to control Diplodia stem-end rot and maintain postharvest quality of citrus fruit - Guimarães, João E.R. [UNESP]; de la Fuente, Beatriz; Pérez-Gago, María B.; Andradas, Cecilia; Carbó, Rosario; Mattiuz, Ben-Hur [UNESP]; Palou, Lluís (Elsevier, 2019)
A large amount of GRAS (generally recognized as safe) salts and concentrations were evaluated in in vitro tests (inhibition of mycelial growth on PDA dishes) against Lasiodiplodia theobromae, the causal agent of citrus Diplodia stem-end rot. Ammonium carbonate (AC, 0.2%), potassium sorbate (PS, 2.0%), potassium carbonate (PC, 0.2%), sodium methylparaben (SMP, 0.1%), sodium ethylparaben (SEP, 0.1%), sodium benzoate (SB, 2.0%), and potassium silicate (PSi, 2.0%) were selected as the most effective. Disease control ability of edible composite coatings formulated with hydroxypropyl methylcellulose (HPMC), beeswax (BW), and these selected antifungal GRAS salts was assessed in in vivo experiments with ‘Ortanique’ mandarins and ‘Barnfield’ oranges artificially inoculated with L. theobromae. Coatings containing 2% PS, 0.1% SEP, or 2% SB were the most effective reducing disease severity (up to 50% reduction) and were also applied to non-inoculated and cold-stored ‘Barnfield’ oranges to determine their effect on postharvest fruit quality. After periods of 21 and 42 d at 5 °C followed by 7 d of shelf life at 20 °C, coatings containing SEP and SB significantly reduced weight loss and did not adversely affect the physicochemical quality attributes (firmness, soluble solid content, titratable acidity, and ethanol and acetaldehyde content) and sensory flavor with respect to uncoated control fruit. Although the internal gas concentration (CO 2 level) of coated fruit increased, the coatings did not induce off-flavors.
Keywords: Citrus coatings; Diplodia stem-end rot; Food additives; Nonpolluting postharvest decay control; Orange, mandarin